The Role of Islamic Social Capital in Strengthening National Governance - Luqman Mahmud; Ayu Nor Azilah Mohamad (Rabbanica: Journal of Revealed Knowledge)
Social capital refers to networks, norms, friendships, values, and mutual understanding that improve an organisation's quality and quantity of cooperation. It has three main components: social networks, social norms, and social rules, all of which help strengthen information flow and harmony among organisation members. Historical factors, such as colonial rule and the division of communities along ethnic lines, hindered the development of social capital in Malaysia during the Malay Sultanate period. The success of social capital in Malaysia depends on mutual acceptance, trust, and commitment within society. In 2023, Malaysia's Prime Minister launched the National Governance Enhancement Movement (GPTN) to strengthen social capital by promoting positive governance values. This study examines the role of social capital in enhancing public service quality under GPTN and explores the concept of social capital from an Islamic perspective, aiming to foster the development of individuals with integrity. The paper uses a literature review to investigate how social capital elements can help organisations achieve governance improvements based on Islamic principles. The findings suggest that Islamic guidelines provide principles for building social capital, indicating that incorporating Islamic-based social capital elements is crucial for fostering a strong national governance culture in Malaysia.